Metal-organic frameworks with 1,4-di(1-imidazol-4-yl)benzene and varied carboxylate ligands for selectively sensing Fe() ions and ketone molecules - Liu, Zhi-Qiang; Zhao, Yue; Zhang, Xiu-Du; Kang, Yan-Shang; Lu, Qing-Yi; Azam, Mohammad; Al-Resayes, Saud I; Sun, Wei-Yin (Dalton transactions : an international journal of inorganic chemistry, 2017)
Four new metal-organic frameworks (MOFs) [Zn(L)(bpdc)]·1.6H 2 O ( 1 ), [Co(L)(bpdc)]·H 2 O ( 2 ), [Ni 3 (L) 2 (bptc) 2 (H 2 O) 10 ]·2H 2 O ( 3 ) and [Cd 2 (L)(Hbptc) 2 ] ( 4 ) were achieved by reactions of the corresponding metal salt with mixed organic ligands of 1,4-di(1 H -imidazol-4-yl)benzene (L) and 4,4′-benzophenonedicarboxylic acid (H 2 bpdc) or biphenyl-2,4′,5-tricarboxylic acid (H 3 bptc). They exhibit varied structures: MOFs 1 and 4 are porous three-dimensional (3D) frameworks, while 2 is an infinite one-dimensional (1D) chain and 3 is a two-dimensional (2D) network. Remarkably, 1 and 4 can act as potential fluorescent materials for sensing Fe( iii ) ions and different ketone molecules with high selectivity and sensitivity. In addition, MOF 1 shows selective adsorption of CO 2 over N 2 . Zn( ii ) and Cd( ii ) frameworks have potential for sensing Fe( iii ) and ketone molecules with high selectivity and sensitivity.